Uma abordagem do tempo em A ostra e o vento de Walter Lima Júnior - Maciel, Sonia Maria Pereira (2006)
In this work, it was searched for the aspects of the process of codification in literature and cinema. The analyzed corpus was composed of the book An oyster and the wind, by the native writer of Ceará Moacir C. Lopes (1982) and the homonym film, an adaptation to the cinema, directed by the motion picture director Walter Lima Júnior (1997). The proposal of this dissertation emerged from the confirmation of a practice, particularly among students, of substituting the reading of a literary work for its corresponding adaptation for the cinema. That practice, which ignores the specifics of each of the languages, solve partially aspects of the content and ignores, totally, questions on the form and the structure, reducing the relevance of the object as an artistic creation. The process of codification in a specific language is done by means of the conventionality of the artistic model in general and of the (artistic) object in particular, which is constituted by the norm, by the norm deviations, by the predictability and the esthetical information. This way, compositional procedures were analyzed in the book and in the film, by having in mind the identification of the responsible elements to the signification of each of the art models. To study the adaptation of a language to the other one, it was started from the semiotic conception of modelization of Iuri M. Lotman, according to which a system of signs organizes itself as a secondary language, as it overcomes itself the natural linguistic level (primary language), getting a peculiar structure to transmit information, what would be impossible by means of an elementary structure strictly linguistic.The element considered responsible to give structure to the artistic language and, therefore, passed to be an information messenger, in the book and in the film, was time. The analysis, in the verbal text, was based on the borderline-table problem in the artistic work (Lotman and Boris A. Uspênski), to establish the modeling value of the categories of beginning and ending and to explain the configuration of time; in the film text, it was based on the binary oppositions (V. V. Ivanov), revealed by the chromatic explored effects. The study of the semiotic mechanisms, in the light of this comparison, makes the own procedures of each type of art more evident. This work, as it approaches the problem of the codification system, in literature and in cinema, delineated some specifics of every one of the systems of signs, making explicit the time element as the main messenger of signification